2010
DOI: 10.4067/s0718-58392010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Genotype on the Anthocyanin Composition, Antioxidant Capacity and color of Chilean Pomegranate (Punica granatum L.) Juices

Abstract: The bioactive compounds content in pomegranate (Punica granatum L.) juice is variable and depends on agronomic factors, genetic and fruit maturity. In Chile, the areas with this crop have increased more than 65% in the last 5 years. This paper aims to determine the phenolic composition, antioxidant capacity and chromatic parameters of juices from eight Chilean pomegranate genotypes (PG2 to PG9), containing red (PG2 to PG6) or pink arils (PG7 to PG9). Color, total polyphenol content (using Folin-Ciocalteu reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
5
31
4
5
Order By: Relevance
“…The destruction of anthocyanin pigments increases with increase in pH (Laleh et al, 2006). The levels of anthocyanin found with our juices were higher than those reported for Iranian (Alighourchi et al, 2008) and Chilean cultivars (Sepú lveda et al, 2010).…”
Section: Nutritional Propertiescontrasting
confidence: 80%
“…The destruction of anthocyanin pigments increases with increase in pH (Laleh et al, 2006). The levels of anthocyanin found with our juices were higher than those reported for Iranian (Alighourchi et al, 2008) and Chilean cultivars (Sepú lveda et al, 2010).…”
Section: Nutritional Propertiescontrasting
confidence: 80%
“…Delphinidin 3,5-diglucoside was the predominant anthocyanin in all cultivars (40.7 mg 100 mL -1 ). Similar results were published by Sepúlveda et al (2010) regarding the anthocyanin content in Chilean pomegranate juice, which reached between 170 and 1342 mg cyanidin-3-glucoside L -1 . Moreover, this group determined the anthocyanin profiles in the juice samples and identified the same six anthocyanins (Cy3,5;Dp3,5;Pg3,5;Cy3;Dp3 and Pg3) as those detected in our study, but at lower concentrations.…”
Section: Anthocyanin Contents Of Pomegranate Juicessupporting
confidence: 78%
“…When comparing our results with Mena et al [3], a similar trend was obtained, namely: Wonderful > Mollar de Elche > Valenciana. In generally, our results were higher than Elfalleh et al [64] who reported values between 28.15 (Gabsi3) and 48.27 (Chetoui) mg Cy 3-glu/l for Tunisian cultivars. On contrary, the values obtained for Wonderful cultivars (254.8 and 293.5 mg Cy 3-glu/l) were within the range reported by Gil et al [6] of 161.9-387.4 mg Cy 3-glu/l for different juices of the same cultivar.…”
Section: Total Monomeric Anthocyanincontrasting
confidence: 55%
“…This range was smaller than that reported by Sepúlveda et al [64], 168-1328 mg Cy 3-glu/l, for genotypes of different regions of Chile. When comparing our results with Mena et al [3], a similar trend was obtained, namely: Wonderful > Mollar de Elche > Valenciana.…”
Section: Total Monomeric Anthocyanincontrasting
confidence: 50%
See 1 more Smart Citation